Effects of temperature on the life history traits of intermediate host snails of fascioliasis: A systematic review - Dube, Agrippa; Kalinda, Chester; Manyangadze, Tawanda; Mindu, Tafadzwa; Chimbari, Moses John (PLoS neglected tropical diseases, 2023)
The impact of climate change has led to variations in various biological processes, leading to altered transmission dynamics of infectious diseases, including snail-borne diseases (SBDs). Fascioliasis is one of the neglected zoonotic tropical snail-borne diseases caused by the trematode of the genus Fasciola. This review focused on laboratory experimental and model studies that evaluate the potential effect of temperature change on the ecology and biology of the intermediate host snails (IHS) of Fasciola. A literature search was conducted on Google Scholar, EBSCOhost, and PubMed databases using predefined medical subject heading terms, Boolean operators, and truncation symbols in combination with direct keywords: Fasciolosis AND Temperature, Lymnaea OR Austropeplea OR Radix OR Galba OR Fossaria OR Pseudosuccinea AND growth, fecundity, AND survival at the global scale. Other search terms used were (Fascioliasis AND Temperature), (Lymnaea AND Temperature), (Austropeplea AND Temperature), (Fossaria AND Temperature), (Galba AND Temperature), (Pseudosuccinea AND Temperature), and (Radix AND Temperature). The final synthesis included thirty-five published articles. The studies reviewed indicated that temperature rise may alter the distribution, and optimal conditions for breeding, growth, and survival of IHS, ultimately resulting in changing the transmission dynamics of fascioliasis. The literature also confirmed that the life history traits of IHS and their interaction with the liver fluke parasites are driven by temperature, and hence climate change may have profound outcomes on the population size of snails, parasite density, and disease epidemiology. We concluded that understanding the impact of temperature on the growth, fecundity, and survival of IHS may broaden our knowledge of the possible effects of climate change and hence inform fascioliasis control programs.